- #1

- 3

- 0

dx)/(x lnx^4)

(dx)/(x 4lnx)

(dx)/(4x lnx)

u = lnx

du/dx = 1/x

(du)(x) = dx

lnx = u dx = (du)(x)

(du)(x)/(4x u)

du/4u

(1/4)ln(u)

(1/4)ln(lnx)

You are using an out of date browser. It may not display this or other websites correctly.

You should upgrade or use an alternative browser.

You should upgrade or use an alternative browser.

- Thread starter ArmiAldi
- Start date

- #1

- 3

- 0

dx)/(x lnx^4)

(dx)/(x 4lnx)

(dx)/(4x lnx)

u = lnx

du/dx = 1/x

(du)(x) = dx

lnx = u dx = (du)(x)

(du)(x)/(4x u)

du/4u

(1/4)ln(u)

(1/4)ln(lnx)

- #2

cristo

Staff Emeritus

Science Advisor

- 8,107

- 73

- #3

HallsofIvy

Science Advisor

Homework Helper

- 41,833

- 963

You mean thelet me know is this correct or no?

dx)/(x lnx^4)

Well, (1/4) ln(ln(x))+ C. And you didn't really need to write "(du)(x)/(4x u)". From du/dx= 1/x, du= dx/x and you can go ahead and substitute du for the dx/x you already have in the integral.(dx)/(x 4lnx)

(dx)/(4x lnx)

u = lnx

du/dx = 1/x

(du)(x) = dx

lnx = u dx = (du)(x)

(du)(x)/(4x u)

du/4u

(1/4)ln(u)

(1/4)ln(lnx)

Share: